FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS TANJUNG PINANG TAHUN 2018 - Putri Dewi Anggraini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
Iron deficiency anemia is anemia caused by the decrease in the total amount of iron in the body so that the reduced iron reserves. Based on the profile of Jambi City Health Department In 2017, the number of pregnant women in 20 healthcentercare the city of Jambi Tanjung Pinang PH Chas priority anemia (Hb 11g%) the highest of 168 (19.5%) of pregnant women. This research is descriptive analytic with cross sectional design. The purpose of this study was to look at the factors associated with anemia in pregnant women in the region work Puskesmas Tanjung Pinang 2018. Research results obtained from 40 respondents, that the proportion of anemic pregnant womenat high riskbased ona parityof 55%, high risk pregnancy spacing is 57.5%, and consumption is less good fetabletis 19.23%. Results of bivariate analysis there are three variables that had a significant relationship with anemia that is parity (0.002), spacing pregnancies (0,001), and the tablet consumption fe (0,022). Based on the resultsof this study concluded that there was a significant relationship between parity, spacing pregnancies and Fe tablet consumption with incidence of anemia in pregnant women in Puskesmas Tanjung Pinang 2018.